Trends in Prescribed Central Nervous System Depressant Medications Among Adults Who Regularly Consume Alcohol: United States 1999 to 2014 - Borodovsky, Jacob T. (Alcohol Clin Exp Res, 2019)
BACKGROUND: Although the risks of using central nervous system depressant (CNS-D) medications with alcohol are well-documented, little is known about trends in prescribed use of these medications among individuals who regularly consume alcohol (i.e., trends in “concurrent use”). We examined changes in the prevalence of prescribed CNS-D medications among individuals who drank alcohol on 52 or more occasions in the past year (“regular drinking”). CNS-D medications included sedative-hypnotics (subclassified as anxiolytics or sleep medications) and opioids. METHODS: We used eight cross-sectional cycles of the National Health and Nutrition Examination Survey (1999-2000 to 2013-2014) from participants age 20 and older (n=37,709). We used log-binomial regression to examine (1) prevalence trends of prescribed CNS-D medication use, (2) trend differences by drinking status, and (3) correlates of CNS-D medication use. RESULTS: Among those who drink regularly, the relative annual increase in prevalence of sedative-hypnotic use was 5.3% (95% CI: 2.7-7.9): anxiolytic and sleep medication use increased annually by 3.7% (95% CI: 0.8-6.7) and 11.2% (95% CI: 6.5-16.0) respectively. Opioid use trends among those who drink regularly were not statistically significant but were non-linear. Differences in CNS-D medication trends between those who drink regularly and those who drink infrequently/abstain were not statistically significant. Those who drink regularly were less likely than those who drink infrequently/abstain to use opioids (adjusted relative risk [ARR]: 0.69, 95% CI: 0.60-0.78) and anxiolytics (ARR: 0.71, 95% CI: 0.61-0.81), but not sleep medications (ARR: 1.04, 95% CI: 0.80-1.35). Those age 40 and older were 2-5 times as likely as those age 20-29 to use sedative-hypnotics. CONCLUSION: Among those who drink regularly, the prevalence of prescribed sedative-hypnotic use increased and prescribed opioid use remained common. These trends indicate that a substantial portion of the population is at risk for alcohol-related adverse drug reactions – particularly those age 40 and older.